1996
DOI: 10.1007/bf00262819
|View full text |Cite
|
Sign up to set email alerts
|

Threshold increases in plasma growth hormone in relation to plasma catecholamine and blood lactate concentrations during progressive exercise in endurance-trained athletes

Abstract: Plasma human growth hormone ([HGH]), adrenaline ([A]), noradrenaline ([NA]) and blood lactate ([La-](b)) concentrations were measured during progressive, multistage exercise on a cycle ergometer in 12 endurance-trained athletes [aged 32.0 (SEM 2.0) years]. Exercise intensities (3 min each) were increased by 50 W until the subjects felt exhausted. Venous blood samples were taken after each intensity. The [HGH] and catecholamine concentrations increased negligibly during exercise of low to moderate intensities r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 21 publications
4
30
1
Order By: Relevance
“…Previous research has suggested that exercise intensity plays a key role, wherein a particular threshold of exercise intensity must be exceeded to elicit GH release (3)(4)(5). However, recent data from our laboratory indicate that, in young men, the magnitude of GH release rises with increasing exercise intensity in a linear doseresponse relationship (as opposed to a threshold relationship) (20).…”
contrasting
confidence: 41%
“…Previous research has suggested that exercise intensity plays a key role, wherein a particular threshold of exercise intensity must be exceeded to elicit GH release (3)(4)(5). However, recent data from our laboratory indicate that, in young men, the magnitude of GH release rises with increasing exercise intensity in a linear doseresponse relationship (as opposed to a threshold relationship) (20).…”
contrasting
confidence: 41%
“…During and after exercise, there are a number of potential stimuli for GH release (lactate, hydrogen ion, catecholamines, core temperature), but the factors that determine the magnitude of GH release remain unclear. Some research have suggested a stimulatory effect of lactic acid on GH release (Chwalbinska-Moneta et al 1996;Langfort et al2001). However, other studies (Kozlowski et al 1983;Zoladz et al 2002) found no causal relationship between blood lactate and GH.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a strong correlation has been observed between the plasma catecholamine and lactate levels during incremental exercise [26]. The stress produced in rats that are forced to run on a treadmill might produce a lot of catecholamine, and as a result the blood lactate concentration could increase even under relatively lowlevel exercise.…”
Section: Discussionmentioning
confidence: 99%